Practical CockroachDB : Building Fault-Tolerant Distributed SQL Databases - Reid, Rob (Apress L.P., 2022)
Get a practical introduction to CockroachDB. This book starts with installation and foundational concepts and takes you through to creating clusters that are ready for production environments. You will learn how to create, optimize, and operate CockroarchDB clusters in single and multi-region environments. You will encounter anti-patterns to avoid, as well as testing techniques for integration and load testing. The book explains why CockroachDB exists, goes over its major benefits, and quickly transitions into installing and configuring CockroachDB. Just as quickly, you'll be creating databases, getting data into those databases, and querying that data from your applications. You'll progress to data privacy laws such as GDPR and CCPA, and learn how CockroachDB's global distribution features can help you comply with ever-shifting data sovereignty regulations. From there, you'll move into deployment topologies, guidance on integration testing and load testing, best practices, and a readiness checklist for production deployments. What You Will Learn Deploy and interact with CockroachDB Design and optimize databases and tables Choose the correct data types for modeling your data Protect data with database and table encryption Achieve compliance with international data privacy regulations Scale your databases in a way that enhances their performance Monitor changes to the data and health of your databases Who This Book Is For Developers and database administrators who want to provide a secure, reliable, and effortlessly distributed home for their data; those who wish to use a modern tool to tackle the kinds of scaling challenges that have previously required dedicated teams of people to solve; anyone who wants to leverage their database to solve non-trivial, real-world challenges while protecting their data and users.